PHOSPHORUS-CALCIUM METABOLISM AND ITS REGULATION IN CHILDREN SUFFERING FROM BRONCHIAL ASTHMA CONSIDERING THE AMOUNT OF BASIC TREATMENT WITH INHALATION GLUCOCORTICOIDS - Колоскова, Олена; Буринюк-Глов’як, Христина (SWorldJournal, 2022)
Topicality. Bronchial asthma (BА) is rather common chronic inflammatory disease among children. Inhalation glucocorticoids (IGC) are considered to be the most effective in the treatment of asthma. They prevent exacerbation, improve the function of the lun